Risk factors for developing colorectal cancer in Japanese patients with ulcerative colitis: a retrospective observational study—CAPITAL (Cohort and Practice for IBD total management in Kyoto-Shiga Links) study I. Issue 1 (1st November 2016) - Yoshino, Takuya; Nakase, Hiroshi; Takagi, Tomohisa; Bamba, Shigeki; Okuyama, Yusuke; Kawamura, Takuji; Oki, Teruki; Obata, Hirozumi; Kawanami, Chiharu; Katsushima, Shinji; Kusaka, Toshihiro; Tsujikawa, Tomoyuki; et al.
Abstract : Background and Aims: Patients with ulcerative colitis (UC) are at risk for developing colorectal cancer (CRC), despite the development of new therapeutic agents. Stratification of the individual UC-patient's risk would be helpful to validate the risk factors for CRC. The aim of this study was to evaluate the risk factors for the development of CRC in a large cohort of patients with UC. Methods: Data were obtained from 12 hospitals in the Kyoto-Shiga region during 2003–2013. We performed a retrospective cohort study of 2137 patients with UC. Results: In total, 60 lesions of CRC were detected in 43 (2.0%) of 2137 patients. 30 of the 43 patients were male. The median age was 53 years. The median duration of disease was 13 years, and 67.4% of these patients had a disease duration >10 years. Of the 43 patients, 34 (79.1%) had extensive colitis. Primary sclerosing cholangitis was detected in 2 patients (4.7%). The median corticosteroids (CS) dose was 6.4 g, and 4 patients were treated with a total of more than 10 g of CS. 18 of these patients underwent more than 1 year CS treatment. Of all 60 CRC lesions, 43 (71.7%) were located in the distal colon and 35 (58.3%) were of the superficial type. Moreover, the stage of CRC was stage 0 or I in 55.8% of the 43 patients with CRC. Multivariate analysis suggested that extensive colitis could be a risk factor for the development of advanced CRC in patients with UC. Conclusions: Our findings indicated that male, extensive colitis, long-term duration of UC and family history of CRC, but not concomitant primary sclerosing cholangitis, are important factors for predicting CRC in Japanese patients with UC. Moreover, long-standing extensive colitis might contribute to the progression of CRC. Further studies are required to establish CRC surveillance in Japanese patients with UC.